INCREASING STUDENTS’ WRITING SKILL IN WRITING PARAGRAPH THROUGH OUTLINE TECHNIQUE OF SECOND GRADE AT SMPN 35 MAKKASAR - Murniati Bongga; Hj Nurfaisah Sahib; Rampeng Rampeng (Lembaga Jurnal FKIP Universitas Bosowa, 2021)
The research aimed to find out whether the use of outline techniques can increase students’ writing skill in writing paragraph descriptive text of second grade at SMPN 35 Makassar. Design of the research was pre experimental method with three steps such as pre-test, treatment and post-test one class. This research was conducted at SMPN 35 Makassar by deciding second grade as population and choosing class VIII.3 which amount 25 students as a sample. Technique of collecting data was done by giving test. In analyzing the numerical data the writer used SPSS 16. Based on the data analysis, the writer can concluded that use outline technique can increasing students writing skill. It can be proved by the mean score of the students in pre-test and post-test. The results of the research showed that the use of outline technique in writing paragraph significantly increased students writing skill in writing paragraph descriptive after did treatment. The mean score increased from 47,52 in pre-test to 69,80 inpost-test. The writer can conclude that the use of the outline technique can increase students’ writing skill of Second Grade of SMPN 35 Makassar.